STRATEGIC DEVELOPMENT OF BETTA FISH AQUACULTURE AT RANR FARM, TASIKMALAYA CITY - Apdan Pebriana; Dudung; Agus Hendar; Yaya Sunarya; Rina Nuryati (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Betta fish (Betta splendens) aquaculture has emerged as a high-potential business within the ornamental fish industry. However, its growth is hindered by various internal and external challenges, including limited digital marketing strategies and increasing market competition. This study was conducted at RANR Farm in Tasikmalaya City and aimed to develop effective strategies using SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM). By evaluating strengths, weaknesses, opportunities, and threats, digital promotion was identified as the top priority strategy, scoring the highest in QSPM (TAS = 2.80). This approach enhances product visibility and market reach significantly. Complementary strategies such as e-commerce training and the formation of local aquaculture communities are also proposed to support business competitiveness. The study emphasizes the urgency of integrating digital marketing tools and fostering collaboration among stakeholders to ensure sustainability and competitiveness in ornamental fish farming.